Factors contributing to longer length of stay in Aboriginal and Torres Strait Islander children hospitalised for burn injury - Courtney Ryder; Tamara Mackean; Kate Hunter; Kurt Towers; Kris Rogers; Andrew J. A. Holland; Rebecca Ivers (BMC, 2020)
Abstract Background Aboriginal and Torres Strait Islander children have higher incidence, severity and hospital length of stay for their acute burn injuries than other Australian children. We examined factors contributing to longer length of stay for Aboriginal and Torres Strait Islander children with an acute burn injury. Methods Burns Registry of Australia and New Zealand admissions of children < 16 years of age between October 2009 and July 2018 were analysed. Descriptive statistics explored patient and injury characteristics; Cox-regression models estimated characteristics associated with longer length of stay. Knowledge Interface methodology and Indigenous research methods were used throughout. Results A total of 723 children were identified as Aboriginal and Torres Strait Islander and 6257 as other Australian. The median hospital length of stay for Aboriginal and Torres Strait Islander children (5 days [CI 5-6]) was 4 days longer than other Australian children (1 day [CI 1-2]). Remoteness, flame burns, high percentage total body surface area (%TBSA) and full thickness burns were factors associated with longer length of stay for Aboriginal and Torres Strait Islander children. Similar prognostic factors were identified for other Australian children along with Streptococcus sp. and Staphylococcus sp. infection. Conclusion Remoteness, flame burns, %TBSA, and full thickness burns are prognostic factors contributing to extended hospital length of stay for all Australian children. These factors are more prevalent in Aboriginal and Torres Strait Islander children, impacting length of stay. Treatment programs, clinical guidelines, and burns policies should engage with the unique circumstances of Aboriginal and Torres Strait Islander children to mitigate inequities in health.